2011
DOI: 10.1080/01495739.2010.511935
|View full text |Cite
|
Sign up to set email alerts
|

Elasto-Viscoplastic Response of Silicon to Femtosecond Laser Heating at Elevated Temperature

Abstract: The elasto-viscoplastodynamics of single-crystalline silicon in response to femtosecond laser pulsing at elevated temperature is studied. Hyperbolic energy transport dynamics is considered in conjunction with the Haasen-Sumino constitutive law to explore the thermo-elasto-visco-plastic response of the silicon material subjected to ultrafast optical heating. A computational scheme with staggered-grids is developed to time-integrate the coupled thermal-mechanical responses of silicon wafer at annealing temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In this case, for a deformable solid body, the specific enthalpy can be written as [24] h ϭ h(T L , e) (2) where e is the strain. It has been shown that [25] ͩ Ѩh Ѩe ͪ…”
Section: Mathematical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, for a deformable solid body, the specific enthalpy can be written as [24] h ϭ h(T L , e) (2) where e is the strain. It has been shown that [25] ͩ Ѩh Ѩe ͪ…”
Section: Mathematical Analysismentioning
confidence: 99%
“…Elastoviscoplastic response of silicon to femtosecond laser heating pulse was investigated by Qi and Suh [2], who indicated that the resulting transverse and longitudinal displacements, along with the normal stress components could be established through well-defined relations with temperatures. Deformation of an axially loaded thermoviscoplastic bar due to laser heating was studied by Wei and Batra [3].…”
Section: Introductionmentioning
confidence: 99%